2011
DOI: 10.1038/ejcn.2010.283
|View full text |Cite
|
Sign up to set email alerts
|

Intake of antioxidants and risk of type 2 diabetes in a cohort of male smokers

Abstract: Background/Objectives: Oxidative stress may induce insulin resistance in peripheral tissues and impair insulin secretion from pancreatic b-cells. Antioxidants are suggested to decrease the risk of diabetes through reduction of oxidative stress. However, only a few studies exist on dietary antioxidants and the risk of type 2 diabetes. We investigated the association of dietary antioxidants with incident type 2 diabetes in the a-Tocopherol, b-Carotene Cancer Prevention Study cohort. Subject/Methods: The study co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
39
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 38 publications
4
39
1
Order By: Relevance
“…Moreover, previous research suggests that smoking increases oxidative stress [16], and that smokers may need a higher intake of carotenoids in comparison with non-smokers to reduce their diabetes risk [9]. One study indeed found reduced diabetes risk with higher serum b-carotene and total carotenoid values in nonsmokers only [9], and a study among male smokers reported no associations of dietary [8] or supplementary [14] b-carotene with diabetes risk. However, two other studies did not confirm such an interaction with dietary carotenoids [7] or supplementary b-carotene [12].…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations
“…Moreover, previous research suggests that smoking increases oxidative stress [16], and that smokers may need a higher intake of carotenoids in comparison with non-smokers to reduce their diabetes risk [9]. One study indeed found reduced diabetes risk with higher serum b-carotene and total carotenoid values in nonsmokers only [9], and a study among male smokers reported no associations of dietary [8] or supplementary [14] b-carotene with diabetes risk. However, two other studies did not confirm such an interaction with dietary carotenoids [7] or supplementary b-carotene [12].…”
Section: Introductionmentioning
confidence: 93%
“…For dietary lycopene, three cohort studies showed no association with diabetes [7,8,15]. Very little research has been performed on other individual dietary carotenoids such as a-carotene, b-cryptoxanthin, lutein, zeaxanthin and the total of carotenoids, and therefore no conclusions can yet be drawn on such intakes [7,8].…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…Studies assessing lutein in relation to metabolic syndrome were all cross-sectional, and thus the inverse relationships that were observed could potentially be explained by reverse causation. Prospective studies in adults that investigated lutein (levels or intake) in relation to risk of type 2 diabetes found inconsistent results (30)(31)(32)(33) , and these studies all had a follow-up period of >10 years, and are thus less prone to risk of reverse causation.…”
Section: Discussionmentioning
confidence: 99%